Clozapine administered repeatedly following pretreatment with ketamine enhances dopamine D2 receptors in the dopamine mesolimbic pathway in mice brain. (10th August 2019) - Szlachta, Marta; Kuśmider, Maciej; Solich, Joanna; Kolasa, Magdalena; Pabian, Paulina; Dziedzicka-Wasylewska, Marta; Faron-Górecka, Agata
Highlights: Mice repeatedly treated with ketamine (KET) display cognitive deficits in ASST model. Clozapine (CLZ) in mice pre-treated with KET increased D2 R mRNA level in the VTA. CLZ in mice pre-treated with KET increased the [ 3 H]domperidone binding in the striatum. CLZ in KET-induced cognitive deficits model enhances biosynthesis of presynaptic D2 R. Abstract: The mechanisms underlying the beneficial effects of clozapine (CLZ) in the treatment of schizophrenia still remains far from clear. In the present work we studied the effect of CLZ on the dopamine D2 receptors (D2 R) in the mouse brain. CLZ was administered after ketamine (KET) in a paradigm strictly matching the one used in KET-induced attentional set-shifting task (ASST). It has been shown previously that CLZ reversed KET-induced cognitive impairments. In the present study we used in situ hybridization to estimate the level of mRNA, together with specific D2 R radioligand, [ 3 H]domperidone binding in the ventral tegmental area (VTA) as well as in the striatum, and observed an increase in the [ 3 H]domperidone binding in the striatum and an increase in D2 R mRNA level in the VTA following repeated (but not acute) CLZ administration in mice pre-treated repeatedly with KET. The obtained results allow for conclusion that CLZ in this experimental paradigm enhances biosynthesis of presynaptic D2 R.